The passive voice perfect tense forms and their distribution in Latvian - Levāne-Petrova, Kristīne (Baltistica, 2019)
This paper deals with the passive voice perfect tense forms and their distribution in Latvian. The data is analysed in the Balanced Corpus of Modern Latvian (LVK2018), Latvian Speech Corpus (LaRKo), and Latvian Speech Recognition Corpus. The auxiliary tikt ‘to get’ (indefinite tenses) and the auxiliary būt ‘to be’ (perfect tenses) in combination with the past passive participle constitute the passive forms in Latvian. However, the passive constructions with two auxiliaries and even with three auxiliaries for the passive forms of the Latvian debitive are also possible and used in Latvian. All aforementioned passive constructions express stative and dynamic perfect forms. Besides, the auxiliary (usually in the third person in the present tense) may be omitted from the predicate. Usually these kinds of passive perfect form variations are not reflected by the Latvian grammars; however, the paradigms of such passive forms are morphologically possible. Therefore, this paper analyses the stative and dynamic passive perfect form distribution in Latvian in the empirical data.